Predictors of Change of Trabecular Bone Score (TBS) in Older Men: results from the Osteoporotic Fractures in Men (MrOS) Study - Schousboe, John T. (Osteoporos Int, 2017)
SUMMARY: Among older men, characteristics that predict longitudinal changes in Trabecular Bone Score (TBS) are different from characteristics that predict changes in bone mineral density (BMD). Most notably, weight loss is strongly associated with concomitant loss in BMD but with concomitant increases in TBS, when measured on Hologic densitometers. INTRODUCTION: Our objective was to compare and contrast predictors of changes in Trabecular Bone Score (TBS), total hip BMD, and lumbar spine BMD. METHODS: Our study population was 3,969 Osteoporotic Fractures in Men (MrOS) cohort participants (mean age 72.8 years) with repeat measures of TBS, lumbar spine and total hip BMD; body mass index (BMI) less than 37 kg/m(2); and no use of bisphosphonate or glucocorticoid medications. TBS was scored (Med-Imaps Software version 2.1) and BMD measured on Hologic densitometers. RESULTS: 1444 men had a TBS decrease > 0.04 units (estimated least significant change for TBS), 795 men had a TBS increase > 0.04 units, and 1730 men had TBS change ≤ 0.04 units over mean follow-up of 4.6 years. Older age was not associated with TBS change, but was associated with greater decline in lumbar spine and total hip BMD. Compared to stable weight, >10% weight loss was strongly associated with an increase in TBS [effect size =1.24 (95% CI: 1.12, 1.36), and strongly associated with a decrease in total hip BMD [−1.16 (95% CI: −1.19, −1.03). Other predictors discordant for longitudinal changes of TBS and BMD included baseline BMI, walk speed, and ACE inhibitor use. CONCLUSIONS: Predictors of changes in TBS are different from predictors of changes in lumbar spine and total hip BMD. At least when assessed on Hologic densitometers, weight loss is associated with subsequent declines in spine and total hip BMD but subsequent increase in TBS. Faster walk speed may protect against loss of hip BMD, but is not associated with longitudinal changes of TBS.